Dissemination and conservation of cadmium and arsenic resistance determinants in Listeria and other Gram‐positive bacteria. Issue 3 (17th March 2020) - Parsons, Cameron; Lee, Sangmi; Kathariou, Sophia
Abstract: Metal homeostasis in bacteria is a complex and delicate balance. While some metals such as iron and copper are essential for cellular functions, others such as cadmium and arsenic are inherently cytotoxic. While bacteria regularly encounter essential metals, exposure to high levels of toxic metals such as cadmium and arsenic is only experienced in a handful of special habitats. Nonetheless, Listeria and other Gram‐positive bacteria have evolved an impressively diverse array of genetic tools for acquiring enhanced tolerance to such metals. Here, we summarize this fascinating collection of resistance determinants in Listeria, with special focus on resistance to cadmium and arsenic, as well as to biocides and antibiotics. We also provide a comparative description of such resistance determinants and adaptations in other Gram‐positive bacteria. The complex coselection of heavy metal resistance and other types of resistance seems to be universal across the Gram‐positive bacteria, while the type of coselected traits reflects the lifestyle of the specific microbe. The roles of heavy metal resistance genes in environmental adaptation and virulence appear to vary by genus, highlighting the need for further functional studies to explain the mystery behind the array of heavy metal resistance determinants dispersed and maintained among Gram‐positive bacteria. Abstract : While exposure to high levels of toxic metals such as cadmium and arsenic is only experienced in a handful of special habitats and ecosystems, Listeria and other Gram‐positive bacteria have evolved an impressively diverse array of genetic tools for acquiring enhanced tolerance to such metals. Here we summarize this fascinating collection of resistance determinants in Listeria monocytogenes and other Listeria spp., with special focus on resistance to cadmium and coresistance to other toxic metals, especially arsenic. We also provide a comparative description of such resistance determinants and adaptations in other Gram‐positive bacteria.